Pengembangan Multimedia Pembelajaran Berbasis Adobe Flash pada Mata Pelajaran PAI Kelas V di SDIT Al-Hasna Klaten - Nanang Gesang Wahyudi; Sri Anitah; Muhammad Akhyar (Teknodika, 2016)
This research aimed to find out: how process of learning in class V SDIT Al-Hasna Klaten, How is the procedure of development learning multimedia subject of Islamic Education class V in SDIT Al-Hasna Klaten, How to effective development of learning multimedia teaching in subjects Islamic education class V in SDIT Al-Hasna Klaten. The method used method of Research and Development (research and development), process development using modification model ADDIE with Borg and gall development model. Stages of development in this study begins with (1) analyzing the needs needed in developing the Product, (2) designing prototypical product, (3) developing the product, (4) implementing the product in the field, and (5) evaluating product’s weaknesses. This reesearch used 15 samples in experimental group (five graders in A class) and 16 samples in control group (five graders in B class). Furthermore, in collecting the data, the researcher used questionnaire and achievement test as the instruments and it was analyzed using Descriptive statistic methods and t-test. The results showed that the media developed has met the worthy and qualified to be used as a learning media. It is seen from the results of expert validation of material with an average of 4.46 and has very good category. Validation of experts media with an average of 4.33 is very good category. According to the students, this multimedia is very good with an average of 4,30. In the test the learning effectiveness, it is known to the average point obtained by the experimental class is 94,66. The average point was higher than the control class 72,81.